Uma mão lava a outra : saneamento básico, política e meio ambiente em Belo Horizonte 1892 – 1973. - Yuri Mello Mesquita (2023)
Our work analyzes the speeches, the projects, the works, and the problems related to the implementation of the modern sewage system and the water distribution in Belo Horizonte between 1892 and 1973. The thesis investigates the impact of sanitation in urban planning, in the nature and in the daily life of the inhabitants of a city in constant transformation. in the capital of Minas Gerais, Brazil, sanitation became a symbol and has contributed to a type of political action. The analyses will focus on the projects and works of sewage and water distribution, the environmental, political and social impacts of the urban growth in the proposed period, principally from 1930 onwards, when the city grew at a faster pace. Among the problems we can emphasize the lack of water, floods, pollution and gastric diseases, a direct consequence of sanitary deficiencies. The case of Belo Horizonte enables the discussion between sanitation, politics, environment and urbanism in a broader context of sanitation networks planning and metropolization in Latin America and in other parts of the world.